El espacio para enterramientos privilegiados en la arquitectura medieval española - Bango Torviso, Isidro G. (Anuario del Departamento de Historia y Teoría del Arte, 1992)
The present work forms part of an investigation about funerary space in the Spanish medieval architecture which will consist of three publications. In the present it is approached the study of the spaces for privileged burials, systematizing the artistic and archaeological facts which we have on function of the documental information. It will denote two great periods, from VI to XI centuries and from XII to XV, with different criterions. On the first of these periods, as it is prohibited to bury inside of church, it is tried to give importance privileged, burials to choose carefully the spaces more significant with relation on the logical circulation of the loyal people or for its communication with the inside of the temple, in this way, emphasizing the space, give prestige to, even more, people who were buried there. During romanic and gothic it is produced the authorization for burying inside of temple. This will cause grave troubles for understanding of interior space, transforming original projects or having to created typologies that anticipate the regular disposition of the funerary spaces.